Heart rate and heart rate variability in horses undergoing hot and cold shoeing - Huangsaksri, Onjira; Wonghanchao, Thita; Sanigavatee, Kanokpan; Poochipakorn, Chanoknun; Chanda, Metha (PLOS ONE, 2024)
Heart rate variability (HRV) is a frequently used indicator of autonomic responses to various stimuli in horses. This study aimed to investigate HRV variables in horses undergoing cold (n = 25) or hot (n = 26) shoeing. Multiple HRV variables were measured and compared between horses undergoing cold and hot shoeing, including the time domain, frequency domain, and nonlinear variables pre-shoeing, during shoeing, and at 30-minute intervals for 120 minutes post-shoeing. The shoeing method interacted with time to change the HRV variables standard deviation of RR intervals (SDNN), root mean square of successive RR interval differences (RMSSD), very-low-frequency band, low-frequency band (LF), the LF to high-frequency band ratio, respiratory rate, total power, standard deviation perpendicular to the line of identity (SD1), and standard deviation along the line of identity (SD2). SDNN, RMSSD, and total power only increased 30 minutes after hot shoeing (all p < 0.05). Triangular interpolation of normal-to-normal intervals (TINN) and the HRV triangular index increased during and up to 120 minutes after hot shoeing (p < 0.05–0.001). TINN increased only during cold shoeing (p < 0.05). LF increased 30 and 60 minutes after hot shoeing (both p < 0.05). SD1 and SD2 also increased 30 minutes after hot shoeing (both p < 0.05). SDNN, TINN, HRV triangular index, LF, total power, and SD2 were higher in hot-shoed than cold-shoed horses throughout the 120 minutes post-shoeing. Differences in HRV were found, indicating increased sympathovagal activity in hot shoed horses compared to cold shoed horses.